Os saberes e fazeres da produção do empadão goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This paper proposes a study on the development of the recipe for Empadão Goiano, a dish closely linked to the food culture and gastronomic heritage of the city of Goiás. Empadão Goiano is a dish built by many hands, having a history that shows an interconnection between different cultures and food practices. Our goal, through this research, is to elaborate an E-book with the main recipes of the Empadão Goiiano. For its elaboration, we used bibliographic research, consulting works related to the themes of heritage, culture and food, following the historical and anthropological views, and interviews carried out in the city of Goiás, through which we aimed to understand these elements from the point of view of cooks, chefs and consumers of the refined dish. With this, an e-book was produced with a gastronomic guide of the Empadão in the city of Goiás, highlighting the masters of the Empadão, its history, different restaurants and recipes. In addition, workshops were held to present the product and the results of the research to the citizens of the City of Goiás, as well as the participants of the research.
Keywords: Empadão; Goiás; Patrimônio; Cultura; Culinária; Patrimony; Food; Culture; CIENCIAS HUMANAS::HISTORIA